2019
DOI: 10.1002/aur.2166
|View full text |Cite
|
Sign up to set email alerts
|

Atypical neural variability in carriers of 16p11.2 copy number variants

Abstract: Copy number variations (CNVs) at the 16p11.2 chromosomal region are associated with myriad clinical features including intellectual disability and autism spectrum disorder. The aim of this study is to determine whether 16p11.2 deletion (DEL) and duplication (DUP) carriers demonstrate a distinct and reciprocal pattern of electroencephalography (EEG) activity as represented by neural variability measures. EEG data were previously collected as part of the Simons Variation in Individuals Project. Variability measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 58 publications
1
11
0
Order By: Relevance
“…This increasing evidence of neural heterogeneity in ASD both at the individual and population level 20,21,47 could explain the failure in identifying biomarkers that are both discriminant with regard to the typical population but also sensitive to variation of clinical symptoms within the spectrum. These results also further support the necessity of developing models that combine multiple clinical scores and neural profiles 20 to better understand the complexity of the spectrum 48 .…”
Section: Discussionsupporting
confidence: 54%
“…This increasing evidence of neural heterogeneity in ASD both at the individual and population level 20,21,47 could explain the failure in identifying biomarkers that are both discriminant with regard to the typical population but also sensitive to variation of clinical symptoms within the spectrum. These results also further support the necessity of developing models that combine multiple clinical scores and neural profiles 20 to better understand the complexity of the spectrum 48 .…”
Section: Discussionsupporting
confidence: 54%
“…A number of VEP studies lowpass filtered responses (≤30 Hz; Al‐Jawahiri et al, 2019; Kovarski et al, 2016, 2019; Milne, 2011)), which might eliminate key distinctions between groups. Here, group differences occurred at high frequencies (≥30 Hz), and an early peak (P 60 ‐N 75 ) correlated with these frequency bands.…”
Section: Discussionmentioning
confidence: 99%
“…Siper et al (2016, 2018) collected tVEPs to a contrast‐reversing checkerboard pattern and suggested that excitatory activity in visual cortex is attenuated in ASD. Other studies have also suggested that high variability in neural responses may be associated with ASD (Al‐Jawahiri et al, 2019; Dinstein et al, 2012; Edgar et al, 2015; Haigh et al, 2015; Milne, 2011; Weinger et al, 2014).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Copy number deletions of this gene such as 16p11.2 deletion are also known to cause PRRT2 ‐related diseases (Dale, Grattan‐Smith, Nicholson, & Peters, 2012; Silveira‐Moriyama et al, 2018; Termsarasab et al, 2014; Weber, Kohler, Hahn, Neubauer, & Muller, 2013). 16p11.2 microdeletion syndrome is a kind of congenital gene deletion disease, with the clinical manifestations as autism, developmental delay, mental retardation, spinal deformity, and a series of neuropsychiatric developmental diseases (Al‐Jawahiri, Jones, & Milne, 2019; Castelein, Steyaert, Peeters, & van Buggenhout, 2019; Hinkley et al, 2019; Li et al, 2018a; Siu et al, 2019). Phenotypic heterogeneity between patients is obvious, and its pathogenic mechanism is not yet clear.…”
Section: Introductionmentioning
confidence: 99%